2011
DOI: 10.1152/ajpheart.00357.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of the PPAR ligand tetradecylthioacetic acid in type 2 diabetic mice

Abstract: Khalid AM, Hafstad AD, Larsen TS, Severson DL, Boardman N, Hagve M, Berge RK, Aasum E. Cardioprotective effect of the PPAR ligand tetradecylthioacetic acid in type 2 diabetic mice. Am J Physiol Heart Circ Physiol 300: H2116 -H2122, 2011. First published March 18, 2011 doi:10.1152/ajpheart.00357.2010.-Tetradecylthioacetic acid (TTA) is a novel peroxisome proliferator-activated receptor (PPAR) ligand with marked hypolipidemic and insulin-sensitizing effects in obese models. TTA has recently been shown to attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Plasma glucose and free fatty acids and liver triglycerides were analyzed as previously described (20). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma glucose and free fatty acids and liver triglycerides were analyzed as previously described (20). …”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative qPCR analysis was performed on LV tissue samples using an ABI PRISM 7900 HT Fast real-time thermal cycler as previously described (18,20). Details about primer/probes sequences are given in supplemented data.…”
Section: Methodsmentioning
confidence: 99%
“…Citrate synthase activity, a commonly used marker of mitochondrial content (9, 10), was measured spectrophotometrically, using a slight modification of the method of Srere (45). Mitochondrial respiration was measured in saponin-permeabilized cardiac fibers by high-resolution respirometry as described earlier (34). Respiration was assayed following addition of glutamate (10 mM) and malate (2 mM) as complex I substrate supply (V0).…”
Section: Methodsmentioning
confidence: 99%
“…However, animal experiments involving pharmacological activation of PPAR in diabetic hearts are inconclusive; potentially due to the specificity of the agent for the various PPAR isoforms. Whilst all, except for tetradecythioacetic acid, TTA, a PPARα agonist that also has potent antioxidant properties 76 demonstrated reduction in circulating FFA and increased glucose oxidation, overall cardiac effects were inconsistent: those employing a PPARγ agonist rosiglitazone and TTA demonstrated improved ischaemic tolerance; 76–78 whereas others using BM17.0744 or 2-(2-(4-phenoxy-2-propylphenoxy)ethyl)indole-5-acetic acid (PPARα and PPARγ agonists, respectively) showed no difference 79 , 80 . It has been suggested that there may be an interaction between substrate availability, PPARα activation and ceramide formation, 70 in which rats treated with a PPARα agonist and fed with high fat diet (34% fat) have increased myocardial ceramide, when the effect was attenuated in rats fed with normal chow diet (3% fat) 81 .…”
Section: How Does the Diabetic Heart Cope With Hypoxia Or Ischaemia?mentioning
confidence: 99%